Analisis Dampak Penerapan Etika Pemasaran Pada PT. Telkom Indonesia - Hilma Harmen; Riza Indriani; Karolin Sitanggang; Nadia Sinurat; Nicko Rajagukguk; Rahel Tambunan; Rexsy Sitanggang; Lija Manalu; Ninda Situmorang (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2024)
This research analyzes the impact of the application of production and marketing ethics at PT Telkom Indonesia (Persero) Tbk, a state-owned company operating in the information and communication technology services sector in Indonesia. Through a qualitative approach, this research aims to understand how PT Telkom applies ethics in the marketing activities of its products, as well as the impact caused by the application of ethics. Secondary data from literature study is used as the main source of information. The results of this research are expected to provide insights for PT Telkom to improve the application of ethics in its operational activities, as well as useful for the government in formulating policies related to marketing ethics in Indonesia. In addition, this research is also expected to help the public in understanding the importance of marketing ethics, and encourage them to choose ethically produced products.